Lactobacillus (LA-1) and butyrate inhibit osteoarthritis by controlling autophagy and inflammatory cell death of chondrocytes - Cho, Keun-Hyung; Na, Hyun Sik; Jhun, JooYeon; Woo, Jin Seok; Lee, A Ram; Lee, Seung Yoon; Lee, Jeong Su; Um, In Gyu; Kim, Seok Jung; Park, Sung-Hwan; Cho, Mi-La (Frontiers in Immunology, 2022)
Osteoarthritis (OA) reduces the quality of life as a result of the pain caused by continuous joint destruction. Inactivated Lactobacillus (LA-1) ameliorated osteoarthritis and protected cartilage by modulating inflammation. In this study, we evaluated the mechanism by which live LA-1 ameliorated OA. To investigate the effect of live LA-1 on OA progression, we administered LA-1 into monosodium iodoacetate (MIA)-induced OA animals. The pain threshold, cartilage damage, and inflammation of the joint synovial membrane were improved by live LA-1. Furthermore, the analysis of intestinal tissues and feces in the disease model has been shown to affect the systems of the intestinal system and improve the microbiome environment. Interestingly, inflammation of the intestinal tissue was reduced, and the intestinal microbiome was altered by live LA-1. Live LA-1 administration led to an increase in the level of Faecalibacterium which is a short-chain fatty acid (SCFA) butyrate-producing bacteria. The daily supply of butyrate, a bacterial SCFA, showed a tendency to decrease necroptosis, a type of abnormal cell death, by inducing autophagy and reversing impaired autophagy by the inflammatory environment. These results suggest that OA is modulated by changes in the gut microbiome, suggesting that activation of autophagy can reduce aberrant cell death. In summary, live LA-1 or butyrate ameliorates OA progression by modulating the gut environment and autophagic flux. Our findings suggest the regulation of the gut microenvironment as a therapeutic target for OA.